Problematika Proses Legislasi di DPR: Analisis terhadap Hambatan dan Solusi dalam Pembentukan Undang-Undang: Issues in the Legislative Process at the House of Representatives: An Analysis of Obstacles and Solutions in the Lawmaking Process - Muhamad Hasbi Alfaruqi; Lilis Satriah (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2024)
This research examines the implementation of the legislative process in the House of Representatives (DPR), which constitutes one of the primary functions within Indonesia's constitutional system. However, the DPR's performance in law-making is frequently questioned due to various obstacles that affect the effectiveness and quality of the legislative products produced. This article aims to analyze the obstacles faced by the DPR in the law-making process and offers practical solutions to address them. The paper employs a normative juridical analytical descriptive approach. Research findings indicate that political, technical, and social obstacles remain the primary factors that slow down and diminish the quality of legislation. The article also proposes implementable solutions to enhance the effectiveness of the legislative process, including improving the quality of academic drafts, strengthening political coordination, and increasing public participation.